Silver diamine fluoride: the science behind the action – a narrative review - Doaa Jamal; Abdullah AlMushayt; Turki Abujamel; Shatha Bamashmous; Nada Bamashmous; Najlaa Alamoudi (BMC Oral Health)
Abstract Background Silver Diamine Fluoride (SDF) is a caries-arresting agent that gained popularity among clinicians and patients due to its effectiveness within hours of application. However, the exact mechanisms underlying its action are not yet fully understood. This narrative review explores the current knowledge of SDF's role in caries management, focusing on its mechanism of action, application methods, and safety. Methods A comprehensive search was conducted in PubMed, MEDLINE, ScienceDirect, and Google Scholar. Out of 820 identified studies, 40 were selected based on relevance to SDF’s chemical properties and clinical application, following duplicate removal and screening of abstracts and full texts. Results Although the literature provides insight into SDF’s benefits in managing caries, its exact mechanism of action and long-term outcomes remain insufficiently understood. Furthermore, variations in the composition of commercially available SDF products, particularly in silver, fluoride, and pH levels, may significantly affect their clinical performance. This variability raises concerns about consistency in therapeutic outcomes and underscores the need for formulation standardization. Conclusion Understanding SDF antimicrobial and remineralization mechanisms is essential for optimizing its clinical use in caries management. While current evidence supports its efficacy, further studies are needed to standardize formulations, refine application protocols, and clarify its long-term therapeutic outcomes.